Structural correlates of preterm birth in the adolescent brain. - Nagy, Z; Ashburner, J; Andersson, J; Jbabdi, S; Draganski, B; Skare, S; Böhm, B; Smedler, A; Forssberg, H; Lagercrantz, H (2009)
OBJECTIVE: The Stockholm Neonatal Project involves a prospective, cross-sectional, population-based, cohort monitored for 12 to 17 years after birth; it was started with the aim of investigating the long-term structural correlates of preterm birth and comparing findings with reports on similar cohorts. METHODS: High-resolution anatomic and diffusion tensor imaging data measuring diffusion in 30 directions were collected by using a 1.5-T MRI scanner. A total of 143 adolescents (12.18-17.7 years of age) participated in the study, including 74 formerly preterm infants with birth weights of